2013
DOI: 10.1002/app.39025
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of polyester polymer concrete using spherical aggregates from industrial by‐products

Abstract: Despite its excellent physical and mechanical properties, polymer concrete has not been widely used owing to its much higher unit price than conventional portland cement concrete. To ensure the economic efficiency of polymer concrete, it is utmost important to reduce the use of polymer binder, which occupies most of the production cost of polymer concrete. Based on the experimental investigations, replacing filler (calcium carbonate) and fine aggregate (river sand) with fly ash and rapid-cooled steel slag (RCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…The mechanical properties of polymer concrete were investigated and it was reported to be more than 18 MPa. Hwang et al replaced filler (calcium carbonate) and fine aggregate (river sand) with fly ash and rapid-cooled steel slag (RCSS), which were obtained from industrial by-products to fabricate polyester polymer concrete [61]. They were found to be effective for improving the strength characteristics and durability as well as the cost efficiency of polymer concrete.…”
Section: Polyester Polymer Concretementioning
confidence: 99%
“…The mechanical properties of polymer concrete were investigated and it was reported to be more than 18 MPa. Hwang et al replaced filler (calcium carbonate) and fine aggregate (river sand) with fly ash and rapid-cooled steel slag (RCSS), which were obtained from industrial by-products to fabricate polyester polymer concrete [61]. They were found to be effective for improving the strength characteristics and durability as well as the cost efficiency of polymer concrete.…”
Section: Polyester Polymer Concretementioning
confidence: 99%
“…1 (строка 2-5), влияние концентрации добавки ОАК незначительно как на морозостойкость, так и на водонепроницаемость. Анализ литературных данных показывает [1][2][3][4][5][6], что наиболее широко используются как компоненты в смесях при получении КМ -аналогов бетона виниловые мономеры, такие как метилметакрилат, стирол, акрилонитрил, трет-бутилстирол, винилацетат. В клеевых композициях с ОАК чаще используют акриловые мономеры [17][18][19][20][21][22].…”
Section: обсуждение результатовunclassified
“…В строительстве и для дорожных покрытий особенно важными являются такие показатели композиционных материалов, как морозостойкость и водонепроницаемость при хорошей прочности. В этом направлении проводятся исследования и испытания новых материалов с включением мономер-полимерных составляющих [1][2][3][4][5][6]. Сочетание свойств бетонов и полимеров позволяет использовать их полезные характеристики, получать композиты, характеризующиеся высокой прочностью, долговечностью, высокой экологичностью и относительно низкой стоимостью.…”
unclassified
“…These PC disadvantages may be: expensive cost of resins used as binder agents, suitable precautions that should be applied to achieve a proper curing of PC, and need to use the high quality aggregates to produce PC, when it is compared with cement-based concrete. In order to reduce the high costs of competitive PC, together with recent environmental concern about wastes that end up in landfills, several researches [ 9 , 10 ] have been conducted to analyze the properties of PC made with industrial byproducts and cement-based concrete residues acting as aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat similar to the resin replacement, aggregates and microfillers have also been replaced by solid wastes from various industrial fields. Demolition materials from concrete and masonry wastes [ 15 ], residual glass from blasting operations [ 16 ], industry development and electrical production wastes such as fly ash or silica fume [ 17 ], crushed polymer concrete and mortar [ 18 ], rapid-cooled slag from the steel production process [ 10 ], or residual sands from foundry industries [ 19 , 20 ] have been studied as mineral aggregates and microfillers in the production of recycled polymer concrete (RPC). These investigations concluded that it is feasible to produce high quality RPC based on recycled solid wastes and performances of resultant materials could be improved by optimizing different variables of the mixtures.…”
Section: Introductionmentioning
confidence: 99%